THE ROLE OF DIALOGICAL SPEECH IN TEACHING RUSSIAN: METHODOLOGICAL ASPECTS - Umarov, Aziz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article explores the role of dialogical speech in the process of teaching Russian as a second language. It examines the key concepts, types, and functions of dialogical speech, emphasizing its importance in developing students' communicative competence. Special attention is paid to methodological approaches and techniques for effectively incorporating dialogues into the learning process, such as role-playing activities and the use of authentic materials. The study also addresses psychological barriers and other challenges faced when teaching dialogical speech. Practical examples of tasks and successful case studies from educational practices are provided in the article.